The Long-Term Forecast of Ghana’s Energy Supply and Demand: Low Emission Analysis Platform (LEAP) Application Model - Dunyo, S. (University of Ghana, 2024)
Ghana, a rapidly evolving nation in West Africa, is confronted with the task of meeting its escalating energy needs while making the shift towards a sustainable, low-carbon energy future. This research endeavours to create a comprehensive long-term projection of Ghana's energy demand and supply using the Low Emission Analysis Platform (LEAP), with a specific focus on identifying pathways for reducing greenhouse gas (GHG) emissions. The study follows a quantitative research approach, gathering historical data on energy supply and demand as well as socio-economic indicators from diverse sources. Utilising the LEAP, the data is analysed to forecast energy demand and supply under two scenarios: business-as-usual (BAU) and mitigation and policy scenarios. The study's findings suggest that Ghana's energy demand is projected to experience significant growth in the coming decades, driven by population expansion, economic progress, and urbanisation. It is expected that household energy demand will be the largest, comprising 63% of the total demand, followed by transport (21.5%), industry (12.3%), and commerce (2.2%) under the mitigation and policy scenario. Similarly, in the baseline scenario, household demand is anticipated to constitute 49.3% of the total, followed by transport (28.2%), industry (19.4%), and commerce (3.1%). In the base year, energy demand was distributed as follows: households (44.1%), industry (16.1%), transport (34.4%), and commerce (5.4%). However, there is a projected insufficient energy supply in the country due to the increasing demand. This would result in an energy gap, as it is estimated that the four energy sectors analysed in this study will consume about 45% of the total energy supply by 2030, decreasing to nearly 40% in 2040 and 35% in 2050. The study emphasises that this gap could be closed by increasing the penetration of renewable energy from sources like solar and wind power to 30% by 2030 and 50% by 2050, reducing Ghana's reliance on fossil fuels. Additionally, the analysis using the LEAP shows that Ghana can significantly reduce its greenhouse gas emissions by implementing low carbon strategies such as promoting renewable energy, adopting energy efficiency measures, and enhancing energy infrastructure. The study's findings have led to several policy recommendations aimed at shaping Ghana's energy future. These recommendations include enhancing renewable energy policies, implementing demand-side management strategies, investing in energy infrastructure, promoting energy efficiency standards, and establishing a carbon pricing mechanism. The insights provided by this study are valuable for policymakers, energy stakeholders, and researchers in Ghana and beyond. The application of the LEAP model has demonstrated its effectiveness in long-term energy planning and policy analysis, particularly in the context of developing countries with limited data availability. This study contributes to the expanding knowledge base on sustainable energy development and climate change mitigation in Africa.
MPhil. Climate Change and Sustainable Development
Keywords: Ghana; West Africa; nation; low-carbon energy